Androgen Deprivation Therapy Combined With Particle Therapy for Prostate Cancer: A Systematic Review - Petersen, Stine Elleberg; Høyer, Morten (Frontiers in Oncology, 2021)
Purpose There is high-level evidence for addition of androgen deprivation therapy to photon-based radiotherapy of the prostate in intermediate- and high-risk prostate cancer. Little is known about the value of ADT in particle therapy of prostate cancer. We are conducting a systematic review on biochemical disease-free survival, overall survival, and morbidity after combined particle therapy and ADT for prostate cancer. Methods A thorough search in PubMed, Embase, Scopus, and Web of Science databases were conducted, searching for relevant studies. Clinical studies on prostate cancer and the treatment combination of particle therapy and androgen deprivation therapy were included. The review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and registered on PROSPERO (CRD42021230801). Results A total of 298 papers were identified. Fifteen papers reporting on 7,202 patients after proton or carbon-ion therapy for localized prostate cancer where a fraction or all patients received ADT were selected for analysis. Three thousand five hundred and nineteen (49%) of the patients had received combined ADT and particle therapy. Primarily high-risk (87%), to a lesser extent intermediate-risk (34%) and low-risk patients (12%) received ADT. There were no comparative studies on the effect of ADT in patients treated with particles and no studies identified ADT as an independent prognostic factor related to survival outcomes. Conclusions The review found no evidence to support that the effects on biochemical disease-free survival and morbidity of combining ADT to particle therapy differs from the ADT effects in conventional photon based radiotherapy. The available data on the topic is limited.